A New Scale for Predicting the Risk of In-hospital Mortality in Patients With Traumatic Spinal Cord Injury - Gong, Yining; Du, Jinpeng; Hao, Dingjun; He, Baorong; Cao, Yang; Gao, Xiangcheng; Zhang, Bo; Yan, Liang (Frontiers in Neurology, 2022)
Purpose: To analyze the relative factors influencing in-hospital mortality in patients with traumatic spinal cord injury (TSCI), and develop a score scale for predicting the risk of in-hospital mortality. Method: We reviewed the medical records from 59 spine centers in mainland China from January 1, 2018, to December 31, 2018. The inclusion criteria were (1) confirmed diagnosis of TSCI, (2) hospitalization within 7 days of injury, and (3) affecting neurological level from C1 to L1. The exclusion criteria were (1) readmission, and (2) incomplete data. Included patients were classified into the survival and non-survival groups according to their status at discharge. Univariate and multivariate logistic regressions were performed to identify the factors related to in-hospital mortality in patients with TSCI. A new scale was developed, and the mortality rate in each risk group was calculated. Results: Of the 3176 participants, 23 (0.7%) died in the hospital, and most of them died from respiratory diseases (17/23, 73.9%). After univariate and multivariate logistic regression analysis, cervical spinal cord injury (odds ratio [OR]=0.264, 95% confidence interval [CI]: 0.076–0.917, P=0.036), abdominal visceral injury (OR=3.778, 95% CI: 1.038–13.755, P=0.044), the American Spinal Injury Association (ASIA) score on admission (A: reference; B:OR=0.326, 95% CI: 0.093–1.146, P=0.081; C:OR=0.070, 95% CI: 0.016–0.308, P<0.001; D:OR=0.069, 95% CI: 0.019–0.246, P<0.001), and surgery (OR=0.341, 95% CI: 0.146–0.796, P=0.013) were significantly associated with in-hospital mortality. Scores for each of the four factors were derived according to mortality rates. The sum of the scores from all four factors was included in the scoring system and represented the risk of in-hospital mortality. The in-hospital mortality risk of the low-risk (0-3 points), moderate-risk (4-5 points), and high-risk groups (6-8 points) was 0.3%, 2.7%, and 9.7%, respectively (P<0.001). Conclusions: Cervical spinal cord injury, abdominal visceral injury, ASIA score on admission, and surgery were significantly associated with in-hospital mortality in patients with TSCI and stable condition. The scale system may be beneficial for clinical decision-making and for communicating relevant information to patients and their families.